Sense of Virtual Place (SOVP): Conceptual Exploration and Initial Empirical Validation - Arora,Vipin; Khazanchi,Deepak (AMCIS2017 - Boston, MA, August 10-12, 2017, 2017)
In this article, we introduce the notion of “Sense of Virtual Place” (SOVP) and explore the factors affecting it. We argue that SOVP can act as a surrogate for user engagement in virtual environments. We develop and validate a SOVP measure, adapting from a widely used measure of Sense of Place (SOP) in the academic disciplines of environmental and social psychology.
Keywords: BIS